Advance Care Planning: Promoting Effective and Aligned Communication in the Elderly (ACP-PEACE): the study protocol for a pragmatic stepped-wedge trial of older patients with cancer - Yuchiao Chang; Joshua R Lakin; James A Tulsky; Elise N Brannen; Michael K Paasche-Orlow; Charlotta Lindvall; Daniel A Gundersen; Areej El-Jawahri; Angelo Volandes; Julie Goldman; Brian Sipin; Michael J Barry; et al. (BMJ Open)
Introduction Advance care planning (ACP) is associated with improved health outcomes for patients with cancer, and its absence is associated with unfavourable outcomes for patients and their caregivers. However, older adults do not complete ACP at expected rates due to patient and clinician barriers. We present the original design, methods and rationale for a trial aimed at improving ACP for older patients with advanced cancer and the modified protocol in response to changes brought by the COVID-19 pandemic.Methods and analysis The Advance Care Planning: Promoting Effective and Aligned Communication in the Elderly study is a pragmatic, stepped-wedge cluster randomised trial examining a Comprehensive ACP Program. The programme combines two complementary evidence-based interventions: clinician communication skills training (VitalTalk) and patient video decision aids (ACP Decisions). We will implement the programme at 36 oncology clinics across three unique US health systems. Our primary outcome is the proportion of eligible patients with ACP documentation completed in the electronic health record. Our secondary outcomes include resuscitation preferences, palliative care consultations, death, hospice use and final cancer-directed therapy. From a subset of our patient population, we will collect surveys and video-based declarations of goals and preferences. We estimate 11 000 patients from the three sites will be enrolled in the study.Ethics and dissemination Regulatory and ethical aspects of this trial include Institutional Review Board (IRB) approval via single IRB of record mechanism at Dana-Farber Cancer Institute, Data Use Agreements among partners and a Data Safety and Monitoring Board. We plan to present findings at national meetings and publish the results.Trial registration number NCT03609177; Pre-results.